Exploratory Analysis of Unemployment Heterogeneity in the Department of Antioquia, Colombia - Álvarez-Valle, William; Torres-Gorrón, John Edwar; Sánchez-Salazar, Cristian; Quintero-Gómez, Luisa Fernanda (Sociedad y Economía, 2024)
IntroductionThe labor market in Antioquia exhibits significant disparities among its municipalities, linked to income, education, infrastructure, and unemployment. This study analyzes these inequalities from a center-periphery perspective, highlighting the Área Metropolitana del Valle de Aburrá as the privileged center in contrast to other subregions.ObjectiveTo explore the heterogeneity of unemployment in Antioquia and understand labor market disparities using advanced statistical techniques.MethodologyMultiple Factor Analysis (MFA) and cluster analysis were employed. The MFA synthesized 2019 data related to demographics, education, wages, and labor market indicators from the department’s 125 municipalities, while cluster analysis grouped the municipalities based on similar characteristics.ResultsThe factorial analysis revealed three main dimensions:• Human capital (47.73% of the variance), dominated by variables related to education, internet access, and wages, with municipalities such as Medellín and Envigado standing out for their high educational and economic indicators.• Demographic configuration (11.41%), linked to factors such as population distribution and the proportion of Afro-descendant population, where high unemployment rates are observed.• Intra-departmental migration and social vulnerability, which jointly explain an additional 11.63%, reflecting migration toward economic centers and labor challenges in peripheral regions.The cluster analysis identified four groups of municipalities with marked regional inequalities.ConclusionsThe study reflects a development model concentrated in the center of the department, perpetuating disparities in the peripheries. Factors such as mismatches between labor supply and demand, and lack of access to essential services, call for inclusive strategies that prioritize infrastructure, education, and employment in the most vulnerable regions.